Pelatihan Career Awarness: Self Knowledge, Educational And Occupational Exploration, And Career Planning Pada Anak-Anak Kelompok Belajar Singajaya Malang - Multisari, Widya; Triyono, Triyono; Rachmawati, Indriyana; Triyono (Universitas Nusantara PGRI Kediri, 2020)
Career awareness is an important thing to grow during elementary school children, before entering the middle school level through a career guidance program. The objective of Career awareness training is to increase student career awareness that includes aspects of self-understanding, education exploration and employment, and career planning. The training was held in Singajaya Learning Group, 27 students. Successful training is identified from changes in understanding, behaviour and actions demonstrated both before and after training. The results of the training provided significant changes for the trainees. Advice from the results of the training that the teachers or turor need to give a career guidance program for early career awareness can be achieved and able to provide a way of success for the future of children.